On the Generation of Instability Tollmien-Schlichting Waves by Free-Stream Turbulence (Advances in Applied Mathematics and Mechanics, 2018)
The beginning of the transition from the laminar to a turbulent flow is usuallythe generation of instability Tollmien-Schlichting (T-S) waves in the boundarylayer. Previously, most numerical and experimental researches focused on generatinginstability T-S waves through the external disturbances such as acoustic waves andvortical disturbances interacting with wall roughness or at the leading-edge of flat-plate,whereas only a few paid attention to the excitation of the T-S waves directly byfree-stream turbulence (FST). In this study, the generating mechanism of the temporalmode T-S waves under free-stream turbulence is investigated by using direct numericalsimulation (DNS) and fast Fourier transform. Wave packets superposed by a groupof stability, neutral and instability T-S waves are discovered in the boundary layer. Inaddition, the relation between the amplitude of the imposed free-stream turbulenceand the amplitude of the excited T-S wave is also obtained.